DESKRIPTIF FAKTOR RESIKO KEJADIAN STUNTING PADA BALITA USIA 12 – 60 BULAN DI WILAYAH KERJA PUSKESMAS SILAYANG KABUPATEN PASAMAN TAHUN 2022 - Kriscillia Molly Morita; Ade Sriwahyuni; Faizatul Rahmadani (Bajang Institute, 2024)
Stunting It is a chronic condition that describes the inhibit of growth due to long-term malnutrition, indicated by the value of Z-Score TB / U less than -2SD based on WHO standards. Stunting in the nicely rotary toddler at the age of 12-60 months. Pasaman district is in 2nd place with stunting prevalence (30.2%) in 2021. The purpose of the study to know the risk factors cause the occurrence stuntingIn the toddlers aged 12-60 months in the work area of Passkeasm Silaway Pataman District. This research was conducted in July 2022. Typical Peniliti Purposive Cluster Random Sampling research design crossectional. The dependent variable is the incident stuntingIn toddlers aged 12-60 months, independent variable, gender, low birth weight, infection status, environmental sanitation, immunization status, feeding pattern, parent work, parental education, economic status. Univariate statistics using frequency distribution. The results of a toddler research with male sex 53.7% suffer stunting. Toddlers have low birth weight (BBLR) 75.2% suffer stunting. Toddlers have infectious diseases in the last 3 months 61.7% suffer stunting. Toddlers that have unneters of environmentally friendly 88.6% suffering stunting. The incomplete toddler of the gas immunization 51.7% sufferstunting. Toddlers with the pattern of dining appropriately not the appropriate 64.4% suffer stunting. Toddlers who have mothers with the status work 82.6% suffer stunting. Toddlers who have mothers with high school status of 57.0% suffering education stunting. Toddlers that have economic status are quite 50.3% suffer stunting. Conclusion of this research that descriptive risk factors incident stuntingIn the greatest toddlers to unhealthy environmental sanitation as much as 88.6%. Suggestions for parents, to keep maintaining environmental sanitation both water cleanliness,Billing and garbage dish to maintain family health